Kebijakan Siber dan Krisis Digital Generasi Muda: Menuju Tata Kelola yang Inklusif dan Ramah Generasi Muda - Widya Agustina; Dian Rianita (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
This study aims to examine the cyber policies implemented by the Indonesian government in light of the impact of digital technology developments on the younger generation, with a view toward achieving inclusive and youth-friendly governance. This study employs a descriptive qualitative method using a critical discourse analysis approach based on van Dijk’s perspective. The research was conducted in three stages: data collection, data analysis, and presentation of results. The data source for this study is Law No. 1 of 2024. The data consists of structured documents collected using the read, observe, and record technique. The results indicate that the cyber policies in Law No. 1 of 2024 mark a shift from a reactive to a proactive approach by prioritizing child protection. This policy expands the scope of protection to include personal data, privacy, and child safety in the digital space, while also affirming the responsibilities of Electronic System Operators. The research findings are expected to enrich understanding of the importance of a policy communication model that is creative, transparent, participatory, and responsive in fostering literacy and critical awareness regarding the use of information technology. Thus, this research is expected to contribute to supporting the realization of a more inclusive digital space governance that is youth-friendly and aligned with the strengthening of moral values and social ethics in community life.